Engineering c-Met-CAR NK-92 cells as a promising therapeutic candidate for lung adenocarcinoma. (February 2023) - Peng, Yan; Zhang, Wenqing; Chen, Yufeng; Zhang, Louqian; Shen, Hongyu; Wang, Zheyue; Tian, Shuning; Yang, Xiaohui; Cui, Daixun; He, Yiting; Chang, Xinxia; Feng, Zhenqing; et al.
Abstract: Mesenchymal-epithelial transition factor (C-Met) has been acknowledged as a significant therapeutic target for treating lung adenocarcinoma (LUAD). However, the potential application of chimeric antigen receptors (CAR)-modified natural killer (NK) cells targeting c-Met in LUAD is rarely explored. In this study, bioinformatic databases were searched and a tissue microarray (TMA) was enrolled to investigate expression status and prognostic role of c-Met in LUAD. Then, four types of c-Met-CAR structures were designed and prepared. The engineering CAR-NK cells containing c-Met-CARs were transfected, verified and characterized. The tumor-inhibitory role of c-Met-CAR-NK cells was finally evaluated in vitro and in vivo. The results demonstrated that c-Met expression elevated and confirmed that high c-Met expression was significantly associated with unfavorable prognosis in LUAD. Then, C-Met-CAR-NK cells were successfully constructed and DAP10 designed in CAR structure was a favorable stimulator for NK cell activation. CCN4 containing DAP10 co-stimulator exhibited the strongest cytotoxicity compared with other CAR-NK cells. Furthermore, CCN4 cells also exerted the prominent tumor-inhibitory effect on xenograft tumor growth. Collectively, this study suggests that DAP10 is a potent stimulator in CAR structure for NK cell activation, and CCN4-based immunotherapy may represent a promising strategy for the treatment of c-Met-positive LUAD. Graphical Abstract: ga1